Reviews in the Neurosciences (De Gruyter, 1987)
Reviews in the Neurosciences provides a forum for reviews, critical evaluations and theoretical treatment of selective topics in the neurosciences. The journal provides an authoritative reference work for those interested in the structure and functions of the nervous system at all levels of analysis, including the genetic, molecular, cellular, behavioral, cognitive and clinical neurosciences.